Răspuns :
a)
x + 12 = 25
x = 25 - 12
x = 13
b)
x + 1,3 = 2,45
x = 2,45 - 1,3
x = 1,15
c)
[tex]x + \frac{1}{4} = \frac{4}{3} [/tex]
[tex]x = \frac{4}{3} - \frac{1}{4} = \frac{4 \times 4 - 3}{3 \times 4} = \frac{16 - 3}{12} = \frac{13}{12} [/tex]
a) x+12=25 b)x+1,3=2,45
x=25-12 x=2,45-1,3
x=13 x=1,15
[tex]x + \frac{1}{4} = \frac{4}{3} \\ x = \frac{4}{3} - \frac{1}{4} \\ amplifici \ cu \ 4 \ prima \ si \ cu \ 3 \ la \ a \ doua \\ x = \frac{16}{12} - \frac{3}{12} \\ x = \frac{13}{12} [/tex]
☆♡SPER CA TE AM AJUTAT ♡☆